MAKNA HIDUP JANDA MUDA PELAKU CERAI GUGAT DI KOTA PEKANBARU - Welly, Nifki Setya; Sari, Genny Gustina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Divorce petition became a phenomenon that occurred in Pekanbaru. The number of divorce petition cases continues to rise from 2014 to 2016 reaching 2915 cases compared to the number of divorce divorce by talak cases that only reached 1010 cases. Divorce petition that done at a young age is not fair because is not easy to live by having a status as a young widow, in addition she has children. The risk of divorce brings big responsibility for the young widow to survive without support of husband in her side. With the new young widow's experience in life's difficulties, this research aims to find out how the young widows who divorce petition in Pekanbaru for the meaning of status, how they interpretation they life and verbal and non verbal communication experience on divorce petition widow in Pekanbaru.This research used a qualitative method with the Phenomenology of suffering viktor frankl to obtain the experience of someone involved in suffering The research subject consists of three young widows who are divorced peition in Pekanbaru City who are chosen by using snowball technique. Data collection is done through in-depth interviews, observation and documentation. And to test validity of data writer use method of extension of participation and triangulation.The result of this reseach is in situation of suffering the young widow tries to divide it and be accepted as part of her life. Young widows interpretation the status he lived as (1) the best way (2) the opportunity to be better and (3) the great woman. The young widow of the divorce suit in Pekanbaru City is the meaning of their life as (1) life is a test and (2) life is an option. While the experience of the young widow's communication experience is categorized into (1) verbal communication experience in the form of advice, praise, to insult (2) nonverbal communication experience of love, sympathy from the opposite sex, guidance, speech tone that understands and glares From people who viewed her negative.Key words : young widow, divorce petition, meaning of life